Therapeutic Prospects of Extracellular Vesicles in Cancer Treatment - Chulpanova, Daria S.; Kitaeva, Kristina V.; James, Victoria; Rizvanov, Albert A.; Solovyeva, Valeriya V. (Frontiers in Immunology, 2018)
Extracellular vesicles (EVs) are released by all cells within the tumor microenvironment, such as endothelial cells, tumor-associated fibroblasts, pericytes and immune system cells. The EVs carry the cargo of parental cells formed of proteins and nucleic acids, which can convey cell-to-cell communication influencing the maintenance and spread of the malignant neoplasm, for example promoting angiogenesis, tumor cell invasion and immune escape. However, EVs can also suppress tumor progression, either by the direct influence of the protein and nucleic acid cargo of the EVs or via antigen presentation to immune cells as tumor derived EVs carry on their surface some of the same antigens as the donor cells. Moreover, dendritic cell-derived EVs carry MHC class I and class II/peptide complexes and are able to prime other immune system cell types and activate an anti-tumor immune response. Given the relative longevity of vesicles within the circulation and their ability to cross blood-brain barriers, modification of these unique organelles offers the potential to create new biological-tools for cancer therapy. This review examines how modification of the EV cargo has the potential to target specific tumor mechanisms responsible for tumor formation and progression to develop new therapeutic strategies and to increase the efficacy of antitumor therapies.